2021
DOI: 10.1186/s13000-021-01068-5
|View full text |Cite
|
Sign up to set email alerts
|

Atypical cells parameter in Sysmex UN automated urine analyzer: feedback from the field

Abstract: Background “Atypical cells” parameter in automated urinalysis has recently been introduced. An instrument capable of measuring quantitative and qualitative features of nuclear and cytoplasmic properties of a cell has the potential to detect cellular atypia. Instruments using flow cytometry have been detecting atypical cells in blood for a long time; yet instruments using the same methodology very lately developed this parameter in urinalysis. Materials and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In a study by Aydın et al, vaginal clue cells were observed when the urine sample of a patient with atypical cell value of 13.7/µL was examined by manual microscopy. 10 Another possibility is that malignancy may be detected in these patients in the future as mentioned above. For this reason, we continue to follow up these patients to perform cystoscopy again if necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Aydın et al, vaginal clue cells were observed when the urine sample of a patient with atypical cell value of 13.7/µL was examined by manual microscopy. 10 Another possibility is that malignancy may be detected in these patients in the future as mentioned above. For this reason, we continue to follow up these patients to perform cystoscopy again if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical cells have enlarged nuclei and a higher nucleus/cytoplasm ratio, as evidenced by side uorescence and scattered light properties. 10 There is no subjective interpretation at any stage of this measurement. Therefore, it gives objective results.…”
Section: Discussionmentioning
confidence: 99%
“…First, only Atyp.C was analyzed as a risk factor for BC, with other known risk factors for BC, such as smoking, heavy use of antibiotics, and common history, omitted. Moreover, urinary Atyp.C values were easily affected by high squamous cell counts and pyuria, and its repeatability was unstable owing to different urinary sample qualities and clinical treatments and interventions in the same patient 15 , 16 . Therefore, using urinary Atyp.C levels alone as a diagnostic index is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of human urothelial cancers have demonstrated that “Atyp.C” can identify cancer cells with a 71.1% agreement with urine cytology, which has some auxiliary significance in the clinical diagnosis of urothelial carcinoma 15 , 16 . The purpose of this study was to explore the relationship between Atyp.C and BC risk in detail, which should lay a foundation for the later optimization of Atyp.C as an early non-invasive diagnostic and monitoring indicator of BC.…”
Section: Introductionmentioning
confidence: 99%
“…The concordance between the results of the two tests was 96.3% and 76.9% in the low- and high-risk groups, respectively. Additionally, Ozgur presented a case in which Atyp.Cs were detected by microscopy when the Atyp.C value was >1/mL [ 27 ]. The results of our study suggest that the Atyp.C value increases with an increase in intracytoplasmic inclusion-bearing cells and severe leukocyturia, but why this occurs has not been explained.…”
Section: Discussionmentioning
confidence: 99%